UNCTAD V and the prospects for the 1980s - Uka Ezenwe (Intereconomics, 1979)
Since the establishment of UNCTAD in 1964 as a permanent organisation for the promotion of the developing countries' trade and development interests, the substantive issues and problems have remained more or less the same. Dr. Ezenwe analyses the reasons why a yawning gap exists between expectations and results and suggests a change of strategy for UNCTAD V.
Keywords: 330; Unctad V